Surgical Outcomes, Complications, and Long-Term Functionality for Free Vascularized Fibula Grafts in the Pediatric Population: A 17-Year Experience and Systematic Review of the Literature - McCullough, Meghan C.; Arkader, Alexandre; Ariani, Rojine; Lightdale-Miric, Nina; Tolo, Vernon; Stevanovic, Milan (Journal of Reconstructive Microsurgery, 2020)
Background In the pediatric population, bony defects of the extremities pose a significant challenge for which free vascularized fibular grafts (FVFGs) represent a valuable reconstructive option. The purpose of this study was to explore surgical outcomes, complications, and long-term functionality of FVFG for this patient group.Methods Using MEDLINE and PubMed databases, studies were identified of pediatric extremity reconstruction using FVFG which reported functional outcomes and/or complications. The operative logs at a tertiary pediatric center were then reviewed for cases of FVFG between January 2000 and 2017. Demographic characteristics, surgical indications, operative details, graft survival, bony union, complications, and functionality of the reconstruction were recorded.Results A total of 366 studies were identified with 23 ultimately meeting inclusion criteria in the systematic review. In the institutional series, 29 patients were included with mean age of 9.7 years (1–17 years). Indications for reconstruction included malignant bone tumor (n = 11), osteomyelitis (n = 9), congenital pseudoarthrosis (n = 6), and osteofibrous dysplasia (n = 3). Major postoperative complications included graft nonunion (24.1%), fracture (17.2%), and hardware failure (17.2%). Thirteen patients (44.8%) experienced delayed complications, while two (6.8%) experienced an immediate complication. Complications occurred in the donor site in 2 cases and the recipient site in all 13 cases. Long-term graft survival was achieved in 27 patients (93.1%), and 23 (79.3%) had full functional recovery, with an average Musculoskeletal Tumor Society score of 90% (60–100%). Mean follow-up was 5.17 years (2–12 years).Conclusion This review and institutional series demonstrate the versatility of FVFG to facilitate limb reconstruction in large defects or serve as a salvage option in complex cases. While immediate and donor-site complications are uncommon, delayed recipient-site complications are frequent, and patients and families should be counseled regarding this expectation. Though technically challenging, excellent long-term graft viability and functional recovery can be achieved in the large majority of patients.
Keywords: flap; vascularized fibula; pediatric; reconstruction